A SISTEM PENDUKUNG KEPUTUSAN DENGANMETODE SIMPLE ADDITIVE WEIGHTING(SAW) DALAM MENENTUKAN BANTUAN SISWA MISKIN PADA SD NEGERI 36 KOTA BENGKULU MENGGUNAKAN VISUAL STUDIO - Kurniawan, Muhammad Andhika; Kanedi, Indra; Fredricka, Jhoanne (Jurnal Media Infotama, 2021)
Programming languages ​​and databases have a very important role in solving various problems faced by humans. With programming languages ​​and databases, human work can be quickly completed by creating a special application in the form of an information system. Currently, the process of selecting prospective BSM recipients is still influenced by the element of subjectivity of those who choose, so it is felt that there is less support for the process. If there is an inaccuracy by the assessment team, then the results will be feared that the provision of assistance to poor students will not be on target. The criteria used are: Parent's Income, Certificate of Inadequacy, Orphanage, Certificate of Good Behavior, and Living in an Orphanage Dormitory. In this research, the application creation tool uses Visual Basic 2015 and uses a database from Microsoft Access.